Report on the dynamic efficiency of trade-related climate policy instruments - Claudio Baccianti; Oliver Schenker (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This report analyses how anti-carbon leakage measures, i.e. Border Carbon Adjustments (BCA), would interact with domestic and foreign firms' R&D investment. The results of a multi- country multi-sector model with endogenous R&D investment are presented, calibrated with data of major world economies. The model also features endogenous market structure in order to embed the effect of changes in market concentration on innovation incentives. Our analysis shows that endogenous R&D investments have significant effects on carbon leakage rates and also increase the effectiveness of BCA schemes. It also shows that understanding the competition-innovation nexus is crucial for a better design of unilateral climate policies.
Additional information: ENTRACTE Project - EU FP7
Keywords: 330